A Preliminary Sketch of Phonology of Limbu Spoken in Sikkim - Sharma, Jyoti (Nepalese Linguistics, 2022)
This paper aims to provide a preliminary sketch of Limbu phonology based on the field recordings conducted under an ongoing Sikkim’s Endangered Language Documentation Project (SELDP) in Sikkim University, India. In the Limbu variety spoken in Sikkim there are 18 consonant phonemes that contrast in the manner and place of articulation. A complementary distribution is observed between various pairs, especially between voiceless and voiced obstruents. Limbu has 11 monophthongs but lacks diphthongs. The canonical form of a syllable is (C)(C)V(C). The rule that regulates syllabication is the Maximal Onset rule. This paper focuses on the analysis of phonological and syllabification rules followed by the language.